2021
DOI: 10.3390/plants10081650
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Mineralization in Dark Grey Calcareous Floodplain Soil Is Influenced by Tillage Practices and Residue Retention

Abstract: Very little is known about the changes that occur in soil organic carbon (SOC) and total nitrogen (TN) under an intensive rice-based cropping system following the change to minimal tillage and increased crop residue retention in the Gangetic Plains of South Asia. The field experiment was conducted for 3 years at Rajbari, Bangladesh to examine the impact of tillage practices and crop residue retention on carbon (C) and nitrogen (N) cycling. The experiment comprised four tillage practices—conventional tillage (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…A similar phenomenon was observed by Zhang et al (2012), where conventional tillage MBC spiked to surpass a no-till treatment before again subsiding. Greater PMC in CT compared with FM adds to evidence suggesting that the disruptive process of tillage would decrease total SOM (Figure 7) (Paustian et al, 2000;Salahin et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…A similar phenomenon was observed by Zhang et al (2012), where conventional tillage MBC spiked to surpass a no-till treatment before again subsiding. Greater PMC in CT compared with FM adds to evidence suggesting that the disruptive process of tillage would decrease total SOM (Figure 7) (Paustian et al, 2000;Salahin et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…It should be noted that assessing the effects of no‐till management on cropland N leaching remains uncertain. Some studies reported that conservation tillage can slightly reduce this hydrological N loss because of the diminished net N mineralization rates (Porwollik et al., 2022; Salahin et al., 2021; Thapa et al., 2018). However, other studies found enhanced nitrate leaching in the reduced‐tillage soils compared with conventional tillage systems, mainly due to the enhanced water drainage caused by greater abundance of macropores (preferential flow channels) and better soil infiltrability (Daryanto et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Its main components are humic acid carbon (HA–C), fulvic acid carbon (FA–C) and humic carbon (HM–C), which are related to soil fertility and fertilization capacity (Madhavan et al, 2017; Wang et al, 2020; Zhao et al, 2019). The soil mineralized carbon is a measure of the amount of soil organic matter that can be decomposed by microorganisms and represents the carbon volume of the mineralized part of the soil to a certain extent (Lewis et al, 2021; Salahin et al, 2021). Carbohydrates are one of the most important and degradable organic components of soil.…”
Section: Discussionmentioning
confidence: 99%